This changes everything : climate Shocks and sovereign bonds - Cevik, Serhan (2020)
Climate change is already a systemic risk to the global economy. While there is a large body of literature documenting economic consequences, there is scarce research on the link between climate change and sovereign risk. This paper investigates the impact of climate change vulnerability and resilience on sovereign bond yields and spreads in 98 countries over the period 1995–2017. We find that the vulnerability and resilience to climate change have a significant impact on the cost government borrowing, after controlling for conventional determinants of sovereign risk. That is, countries that are more resilient to climate change have lower bond yields and spreads relative to countries with greater vulnerability to climate change. Furthermore, partitioning the sample into country groups reveals that the magnitude and statistical significance of these effects are much greater in developing countries with weaker capacity to adapt to and mitigate the consequences of climate change.